Hubungan Komunikasi dengan Pencegahan HIV AIDS pada Pasien Poli Gigi Puskesmas dan Rumah Sakit di Kabupaten Bulukumba - Iriani Masjidi; Andi Surahman Batara; Andi Asrina (PT.Mantaya Idea Batara, 2025)
An infection that attacks the immune system is known as human immunodeficiency virus (HIV). The most severe condition of this disease is known as acquired immune deficiency syndrome (AIDS). HIV damages leukocytes in the body that function to reduce immunity. This study examines the relationship between HIV AIDS prevention and communication in dental polyclinic patients at hospitals and health centers in Bulukumba Regency in 2024. Based on information collected from surveys, interviews, observations, and documentation, this study uses a cross-sectional study approach with a quantitative type to analyze the relationship between variables. In this study, the population was all employees of the Dental Polyclinic, Health Centers and Hospitals in Bulukumba Regency, totaling 55 dental polyclinic officers. The sample collection method used was purposive sampling. Based on the results of the study, the chi-square test was used to determine the results of the statistical test. Based on the p-value (0.001 <? = 0.05), Ha was accepted and H0 was rejected. In 2024, there was a relationship between HIV AIDS prevention and communication in dental polyclinic patients at hospitals and health centers in Bulukumba Regency. To reduce the number of cases in Bulukumba Regency, dental polyclinic officers are required to carry out promotional and educational efforts as early as possible to patients and the community